2010
DOI: 10.1007/s00418-010-0675-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal changes of SDF1 and its CXCR4 receptor in the dorsal root ganglia following unilateral sciatic nerve injury as a model of neuropathic pain

Abstract: There is a growing evidence that chemokines and their receptors play a role in inducing and maintaining neuropathic pain. In the present study, unilateral chronic constriction injury (CCI) of rat sciatic nerve under aseptic conditions was used to investigate changes for stromal derived factor-1 (SDF1) and its CXCR4 receptor in lumbal (L4-L5) and cervical (C7-C8) dorsal root ganglia (DRG) from both sides of naïve, CCI-operated and sham-operated rats. All CCI-operated rats displayed mechanical allodynia and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 72 publications
(88 reference statements)
7
56
0
Order By: Relevance
“…Through binding to its G-protein-coupled receptor (GPCR) CXCR4, CXCL12 plays a vital role in nociceptive signal processing (Reaux-Le Goazigo et al 2012). Previous studies documented that, in some murine models of neuropathic pain, CXCL12 and CXCR4 are increased in the dorsal root ganglion or spinal cord (Bhangoo et al 2007;Dubovy et al 2010;Knerlich-Lukoschus et al 2011). Furthermore, our recent study has also shown that the expression of CXCL12 and CXCR4 was constitutively up-regulated in the spinal cord of bone cancer rats, and spinal blocking CXCR4 could attenuate BCP through suppressing CXCR4-mediated astrocytic and microglial activation (Shen et al 2014).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Through binding to its G-protein-coupled receptor (GPCR) CXCR4, CXCL12 plays a vital role in nociceptive signal processing (Reaux-Le Goazigo et al 2012). Previous studies documented that, in some murine models of neuropathic pain, CXCL12 and CXCR4 are increased in the dorsal root ganglion or spinal cord (Bhangoo et al 2007;Dubovy et al 2010;Knerlich-Lukoschus et al 2011). Furthermore, our recent study has also shown that the expression of CXCL12 and CXCR4 was constitutively up-regulated in the spinal cord of bone cancer rats, and spinal blocking CXCR4 could attenuate BCP through suppressing CXCR4-mediated astrocytic and microglial activation (Shen et al 2014).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Using IR, CXCL12 and CXCR4 have been detected in spinal neurons and astrocytes. Recent studies have shown that CXCL12 and CXCR4 expression is upregulated in the L4-5 DRG by unilateral chronic constriction injury of the rat sciatic nerve [17] and i.p. administration of the antiviral agent 2 0 ,3 0 -dideoxycytidine [34].…”
Section: Sni Upregulates Cxcl12 and Its Cognate Receptor Cxcr4 In Thementioning
confidence: 99%
“…They are widely distributed and constitutively expressed in small amounts in small-and medium-sized dorsal root ganglia (DRG) neurons and glia (satellite cells) and in the spinal cord [15,16]. The administration of antiretroviral drugs or unilateral chronic constriction injury of the sciatic nerve leads to the development of neuropathic pain, which is correlated with the upregulation of both CXCL12 and CXCR4 in the DRG [17,18]. Intrathecal (i.t.)…”
Section: Introductionmentioning
confidence: 99%
“…Following nerve injury there is an invasion of immune cells into the nervous system that is promoted largely by the Wallerian degeneration of the injured nerve as well as by damage of the tissue surrounding the nerve (Chung et al, 2007;Dubovy et al, 2007;Hu and McLachlan, 2002). The immune cells alter the neuronal environment in part by changing the level of various cytokines/chemokines produced by the immune cells and by the neurons and glial cells in response to those released by the immune cells (Austin and MoalemTaylor; Brazda et al, 2009;Dubovy et al, 2006;Dubovy et al, 2010a;Dubovy et al, 2010b). Since some of the immune mediators have been shown to contribute to neuropathic pain by altering the excitability of both primary and secondary sensory neurons one approach that has been investigated to treat/prevent chronic pain is to pharmacologically alter their production.…”
Section: Peripheral Nerve Injury Alters the Dorsal Root Ganglia Envirmentioning
confidence: 99%